Lead Induced Oxidative Stress and Alteration in the Activities of Antioxidative Enzymes in Rice Shoots - Thakur, Sveta; Singh, Lakhveer; Zularisam, A. W.; Mimi Sakinah, A. M.; M. F. M., Din (Springer, 2017)
Physiological responses of Oryza sativa L. to lead excess (10 and 50 μM) were studied in hydroponic system after 48- and 96-h exposure. The Pb accumulation in stressed rice shoots was concomitant with increased metal concentration in the growth media and duration of exposure. Pb stress resulted in enhanced lipid peroxidation accompanied by altered activities of antioxidants. A substantial increase in α-tocopherol content of the Pb stressed rice shoots was observed suggesting its important role as an antioxidant. Among the antioxidant enzymes studied, the activities of superoxide dismutase (SOD) and ascorbate peroxidase (APX) increased in Pb-treated rice shoots, while that of catalase (CAT) was declined. Activity of an important ascorbate-glutathione cycle enzyme glutathione reductase (GR) also increased significantly in Pb-treated shoots. Results suggest that Pb toxicity results in induction of oxidative stress in rice shoots and α-tocopherol accumulation and upregulation of SOD, APX, and GR activities play an effective role in acclimatization to Pb stress.